Keefektifan Model Make A Match Berbantuan Papan Perkalian Terhadap Pemahaman Konsep Perkalian (Universitas Negeri Semarang, 2021)
Abstract The mathematics learning in the second grade of Srikandi Cluster Elementary School Semarang were still using conventional models, peer tutors, binggo games, and a lack of innovation in learning media. This study aimed to test the effectiveness of the make a match learning model assisted by the multiplication board media compared to the blackboard-assisted model on understanding the concept of multiplication. This research was an experimental study with a quasi experimental design. The sampling technique used random sample sampling. The data collection techniques were interviews, documentation and tests. The data analysis technique used the learning mastery test, hypothesis test and n-gain test. The results of the learning mastery test of the experimental class were more than 75%, amounted to 76,77% while the control class only got a score of 66,33%, the results of the hypothesis test showed that tcount (19,690)> ttable (2.002), and the results of the n-gain test for the experimental class were higher than the control class, which was 0.711 included in the high category, while the control class was 0.194 included in the low category. So it can be concluded that the make a match learning model assisted by the multiplication board media in the experimental class was effective than the blackboard-assisted learning model. Abstrak Pelaksanaan pembelajaran matematika kelas II SDN Gugus Srikandi Semarang cenderung menggunakan model konvensional, tutor sebaya, penerapan permainan binggo, serta kurangnya inovasi media pembelajaran. Penelitian ini bertujuan untuk menguji keefektifan model pembelajaran make a match berbantuan media papan perkalian dibandingkan model kelas kontrol berbantuan papan tulis terhadap pemahaman konsep perkalian. Penelitian ini adalah penelitian eksperimen menggunakan quasi experimental design. Teknik pengambilan sampel menggunakan sample random sampling. Teknik pengumpulan data wawancara, dokumentasi dan tes. Teknik Analisis data yang digunakan adalah uji ketuntasan belajar, uji hipotesis dan uji n-gain. Hasil uji ketuntasan belajar kelas eksperimen lebih dari 75% yaitu 76,77% sedangkan kelas kontrol 66,33%, hasil uji hipotesis menunjukkan thitung (19,690) > ttabel (2,002), dan hasil uji n-gain kelas eksperimen lebih besar daripada kelas kontrol yaitu 0,711 termasuk kategori tinggi, sedangkan kelas kontrol 0,194 termasuk kategori rendah. Sehingga dapat disimpulkan bahwa model pembelajaran make a match berbantuan media papan perkalian pada kelas eksperimen efektif daripada model pembelajaran kelas kontrol berbantuan papan tulis.